Evaluating erosion control practices in an actively gullying watershed in the highlands of Ethiopia. Issue 13 (11th July 2018) - Ayele, Getaneh K.; Addisie, Meseret B.; Langendoen, Eddy J.; Tegegne, Nigus H.; Tilahun, Seifu A.; Moges, Mamaru A.; Nicholson, Charles F.; Steenhuis, Tammo S.
Abstract: Soil erosion, with significant contributions from gullies, is a serious problem in the Ethiopian highlands. The objective of this paper is to examine patterns of discharge and sediment transport in the Ethiopian highlands, and to provide an initial assessment of whether soil and water conservation practices (SWCP) can reduce sediment loads in watersheds with actively eroding gullies. The study was conducted in the 414‐ha Ene‐Chilala watershed with a unimodal sub‐humid monsoon climate and actively eroding gullies in the valley bottoms. In 2013 and 2014, the local community was mandated to install upland infiltration furrows and farmers voluntarily rehabilitated six gully heads and protected 16 m of eroding stream banks. Discharge and sediment concentration were measured in two upslope watersheds and at the outlet. Since median infiltration capacity in the uplands was always greater than the rainfall intensity, saturation excess and interflow were main runoff pathways. After 175 mm cumulative rainfall, the groundwater table reached the surface in the valley bottoms, restricting infiltration, and runoff was generated as saturation excess overland flow and flowed through active gullies out of the watershed. Upland rill erosion on ploughed land early in the rain phase, and gully erosion in saturated valley bottoms thereafter, were sources of sediment in the rivers. The mandated infiltration furrows installed on the contour overtopped and damaged cropland. The off‐contour furrows increased streamflow. Gully rehabilitation of an upland gully effectively reduced stream sediment concentration in the upland weir. However, there was little benefit at the watershed outlet since the stream picked up the unconsolidated sediment from the failing banks in the downstream porting of the watershed. Therefore, soil conservation programs that in addition to installing upland practices, rehabilitate the main sediment source (gullies) appear to be the most effective approach to reducing in‐stream suspended sediment concentrations. © 2018 John Wiley & Sons, Ltd. Abstract : Active gullies increase sediment concentrations in streams, rendering upland soil conservation practices less effective. Conservation programs treating the whole watershed including gullies are the most effective.